Bank capital ratios in the 1990s: cross-country evidence - De Bondt, Gabe J.; Prast, Henriette M. (PSL Quarterly Review, 2013)
This study aims at assessing empirically the determinants of changes in risk-weighted bank capital ratios in the 1990s in Germany, France, Italy, the Netherlands, the UK and the US. Both bank-specific characteristics, factors at the banking industry level and the degree of undercapitalization are found to be relevant for bank capital ratios. The results suggest that in most cases either banks assess the risk of their portfolio as being higher than the outcomes generated by the Basel Capital Accord risk weighting scheme, or they need to take additional country- or bank-specific capital requirements into account when setting capital ratios. In all countries commercial banks face a downward pressure on their capital ratios due to an intensified competition. Finally, capital regulation seems to be effective in influencing bank capital ratios. JEL Codes: G21, G28